Heroism and Hubris: A Literary Analysis of Risk and Masculinity in Krakauer’s Into Thin Air - Thapa, Hukum (Literary Studies, 2026)
This study analyzes Jon Krakauer’s Into Thin Air through the lens of literary and gender theory, focusing on how the constructs of heroism and masculinity are both upheld and dismantled in the context of high-risk mountaineering. Drawing on R.W. Connell’s theory of “hegemonic masculinity,” the study reveals how Everest becomes a performative space where climbers enact dominant ideals of male strength, stoicism, and control. Simultaneously, Krakauer’s narrative exposes the fragility of these ideals when confronted with extreme conditions, mortality, and ethical dilemmas. Judith Butler’s concept of “gender performativity” further supports the analysis of how masculinity is not innate but constantly reiterated through action, especially under duress. Additionally, the study incorporates Ulrich Beck’s “risk society theory” to contextualize how modern adventure tourism commodifies risk, turning personal conquest into a public spectacle. Krakauer’s use of first-person narration is examined through Gérard Genette’s narratological theory, revealing how the interplay of subjectivity and retrospection shapes the reader’s perception of heroism and failure. Ultimately, this paper argues that Into Thin Air functions as both a personal memoir and a broader critique of masculine identity in extreme environments. It contributes to the fields of adventure literature, gender studies, and cultural criticism by interrogating the ethical and psychological implications of high-risk masculinity in the age of commercialized adventure.